Big five personality traits and well-being: Evidence from university students of India - Singhal, Abhishek; Nema, Priyanka; Chakraborty, Abhinandan; Kumar, Prabhat (The journal of contemporary issues in business and government, 2021)
Agreeableness amongst individuals is known to form a significant personality dimension impacting well-being. The Agreeableness trait and extraversion, and Neuroticism are given the main focus here as a prognosticator of the emotional element of well-being amongst Indian Students. Centered upon Big Five (B5) Personality test and SWB, Students (N=320) were rendered with questionnaires. Utilizing correlation, multiple regression analysis, in addition to structural equation modeling, the outcomes were examined. The Outcomes exhibited that the Neuroticism trait directly links to Negative Emotions (NE), while Extraversion is directly related to Positive Emotions (PE). Especially, Agreeableness is related to positive-negative emotions together with balance emotions.